Integration of Learning Organization Principles in Muhammadiyah Education: A Case Study of Elementary and Middle Schools in Palembang, Indonesia - Zulkipli Jemain; Idham Kholid; Abid Djazuli; Subandi Subandi (STAI Hubbulwathan Duri, 2025)
Muhammadiyah education is evolving as a progressive Islamic learning ecosystem. To sustain this development, effective organizational management is essential. This study explores the integration of Learning Organization principles, as defined by Peter Senge—Systems Thinking, Personal Mastery, Mental Models, Shared Vision, and Team Learning—within Muhammadiyah Elementary and Secondary Schools in Palembang City. A qualitative case study approach was employed, involving in-depth interviews, participatory observation, and policy document analysis across selected Muhammadiyah schools in Palembang. Findings reveal that Learning Organization principles are beginning to be adopted, though implementation remains suboptimal. Systems Thinking is evident in school management practices, yet institutional synergy is limited. Teacher training promotes Personal Mastery, but reflective learning has yet to be embedded. Mental Models present a barrier, as some educators cling to traditional pedagogies. While a Shared Vision has been formally articulated, it lacks operational internalization. Team Learning shows initial growth but requires policy reinforcement. The partial integration of Learning Organization elements highlights the potential for deeper cultural and structural transformation. Limitations in collaboration, reflection, and internal alignment indicate areas needing strategic attention. To enhance the effectiveness of Muhammadiyah’s educational model, this study recommends strengthening teacher development programs, revising internal policies, and leveraging digital tools to foster adaptive learning environments. These steps can reinforce Muhammadiyah’s position as a leader in progressive Islamic education in Indonesia.